"I am a little superhero!": a pilot play-based group to enhance self-esteem of children from low-income families in Hong Kong. Issue 2 (3rd April 2021) - Wong, Jessie Ming Sin
ABSTRACT: Self-esteem is crucial to children's psychological health. However, several factors can impact the development of self-esteem, including families' income. The purpose of this article is to describe the development, implementation, and preliminary evaluation of a pilot play-based group intervention that aimed at enhancing the self-esteem and social skills of primary school-aged children from low-income families in Hong Kong. Seven children attended six 1.5-hour weekly sessions. They completed the Rosenberg Self-Esteem Scale (RESE) before and after the implementation of the group. Participant observation and an exit questionnaire were also used to collect the data for evaluation. By the end of the group, children already showed mild but significant improvement in RESE scores. They also demonstrated enhanced self-understanding and social skills. The "superhero" theme and play-based approach successfully attracted children's interests and provided a basis for the development of more comprehensive programs to boost the wellbeing of disadvantaged children from diverse contexts.